Using a calibrated multi-zone building model to analyse the impact of occupant behaviour on building performance - Wang Yuanchen; Maixiwuer Aini; Schwede Dirk; Stergiaropoulos Konstantinos (E3S Web of Conferences, 2022)
Building performance simulation has been commonly used for performance-based building design. However, the simulation accuracy is closely related to the model and input parameters regarding the building physics and occupant behaviour. To check and improve the accuracy of the simulation, the model usually needs to be calibrated using measured data. Uncertain parameters are adjusted in this process to reduce the discrepancy between simulation and measurement results. Although occupant behaviour has a significant impact on building performance, it has not been considered a key component of model calibration in previous studies. Model calibration using only indoor environmental and energy consumption data without considering occupant behaviour is unreliable. In this context, a step-by-step model calibration approach is proposed in this study to optimise the estimated parameters in typical operational scenarios where occupant behaviour can be conveniently determined. A case study shows that although the simulation results for apartment energy use are similar before and after model calibration, differences can be observed in the evaluation of indoor air quality and thermal environment. Simulation results using occupant behaviour based on design standards are significantly deviated from the measured values, compared to that using actual occupant behaviour.